Effect of MWCNT on mechanical characterization of glass/carbon hybrid composites. (October 2022) - Swikker, K. Robinston Jeyasingh; Kanagasabapathy, H.; Neethi Manickam, I.
In this present study, the mechanical properties of Glass/Carbon hybrid composite reinforced with epoxy resin with and without multi-walled carbon nanotubes (MWCNT) were investigated. The composite under Experimental analysis were fabricated by using both Hand layup and Vacuum bag moulding processes. The main purpose of including MWCNT as a reinforcement material with epoxy is to reduce the existence of voids or cavities and to enhance the mechanical properties of Glass/Carbon hybrid composites. Because of their extraordinary mechanical properties and high aspect ratio, MWCNTs are considered to be ideal candidates for polymer reinforcement. The percentages of MWCNT selected for the study are 2%, 3% and 4% with the hybrid composites. The effect of MWCNT on mechanical properties such as tensile strength, compressive strength, flexural strength, impact strength, hardness and percentage of water absorption of the hybrid composites were determined as per American Society for Testing and Materials (ASTM) standards. The result from the study shows that the mechanical properties of hybrid composites were improved with the addition of small amount of MWCNT than without MWCNT. The fractured specimen from Tensile test is examined by using Energy Dispersive X-Ray Analysis (EDX)to study the alignment of the fibres, fibre-matrix adhesion, voids and filler agglomeration. This investigation provides proper guidelines to designers on enhancing mechanical properties of Glass/Carbon composite structures through MWCNT reinforcement for Aircraft structural components.